EFEKTIFITAS PEMBERIAN WEDANG JAHE TERHADAP FREKUENSI MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I DI KABUPATEN BENGKULU UTARA TAHUN 2017 - Iluh Meta Indrayani; Rialike Burhan; Desi Widiyanti (Poltekkes Kemenkes Jakarta III, 2018)
Emesis gravidarum is a usual complaint that is often experienced by the first trimester pregnant women, and coul develop become hyperemesis gravidarum thus increasing the risk of pregnancy. Ginger is kind of herbs which has been known to prevent nausea vomiting. The purpose of this study is the effectiveness of giving wedang ginger to the frequency of nausea and vomiting in pregnant women trimester I. The design of this research is Quasi experiment with One Group Pre test-Post test design. The sampling technique used purposive sampling with the sample of 10 first trimester pregnant women who experience emesis gravidarum. This research was conducted at Work Area of ​​Air Lais Puskesmas of North Bengkulu Regency on January 5, 2018 until February 6, 2018. Analysis of difference of frequency of nausea vomiting before and after intervention using Paired Sample T-Test. The results of this study indicate the average frequency of nausea vomiting pregnant women trimester I before given wedang ginger of 9.30. While the average frequency of nausea vomiting trimester pregnant women I after given ginger wedang of 4.50. The result of bivariate analysis showed that there was difference of mean of nausea vomiting frequency before and after intervention of wedang ginger equal to 4,80 with p = 0.000. Expected for the community can take advantage of ginger wedang as an alternative treatment before using antiemetic drugs, and can process other variants of ginger plants that can be used to lower the emesis gravidarum frequency.